If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy(5xy) + 3xy(1) = equation Remove parenthesis around (5xy) 3xy * 5xy + 3xy(1) = equation Reorder the terms for easier multiplication: 3 * 5xy * xy + 3xy(1) = equation Multiply 3 * 5 15xy * xy + 3xy(1) = equation Multiply xy * xy 15x2y2 + 3xy(1) = equation Reorder the terms for easier multiplication: 15x2y2 + 3 * 1xy = equation Multiply 3 * 1 15x2y2 + 3xy = equation Reorder the terms: 3xy + 15x2y2 = equation Solving 3xy + 15x2y2 = aeinoqtu Solving for variable 'x'. Reorder the terms: -1aeinoqtu + 3xy + 15x2y2 = aeinoqtu + -1aeinoqtu Combine like terms: aeinoqtu + -1aeinoqtu = 0 -1aeinoqtu + 3xy + 15x2y2 = 0 The solution to this equation could not be determined.
| 17x-3-12=.2(25x-10) | | 3xy(5xy)+3xy(1)= | | 16t^2+150t+20=0 | | 5x+2=36 | | .5x-.625=.75x+.375 | | 2x(x-4)+x(3-2x)= | | 13r+4-7r= | | -2+ln(x-4)=4 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 2B-6=4B | | 3-(3x-8)=4y-5 | | (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n |